Structure and Obstacles in Developing Public Healthcare Services for Pregnant Women through the Collaboration between Thong Saen Khan Subdistrict Municipality, Thong Saen Khan District, Uttaradit Province, and the Private Sector - Tantijariyapan, Supattra (SOCIAL SCIENCES RESEARCH AND ACADEMIC JOURNAL, 2025)
This research article aims to investigates the structure of public health services provided to pregnant women by local government organizations and private sectors in connection with national-level agencies. It also aims to analyze the obstacles in developing local public health services for pregnant women through a partnership between Thong Saen Khan Subdistrict Municipality and the private sector. This study employs a qualitative research approach, integrating document analysis with structured interviews. Key informants working in healthcare services were selected through purposive sampling, resulting in 6 groups comprising a total of 37 participants. Data were analyzed using content analysis. Findings revealed the following: The public health service structure in Thailand, facilitated through public-private collaboration, is predominantly vertical, with the National Health Security Office (NHSO) functioning as the policy-level authority. For the Thong Saen Khan Subdistrict Municipality, the local public health service is managed through the Thong Saen Khan Subdistrict Health Security Fund. This fund includes a committee comprising by virtue of their position from the Thong Saen Khan Municipality personnel and appointed external members who are responsible for fund management. This structure reflects a matrix organizational model, integrating both vertical and horizontal approaches. The study identified six primary obstacles: inadequate funding, struggles in soliciting donations from outside sources, disjointed collaboration among public and private sectors, inefficiencies in resource allocation and oversight, inherent restrictions of small-scale administrations lacking specialized health departments, and the absence of a comprehensive health plan within the local health security fund. Furthermore, nearby prenatal care facilities grapple with shortages of staff and infrastructure, which hampers their capacity to provide adequate assistance to expectant mothers. The research findings emphasize that Thailand’s public health service structure, developed through collaboration between the public and private sectors, is characterized by centralized administrative authority. Consequently, private sector participation in local public health service delivery must adhere strictly to nationally established mechanisms. For municipalities, as legal entities, to promote private sector involvement in enhancing the quality of such services, it is essential to establish appropriate mechanisms under the relevant legal framework while considering the six identified challenges previously discussed.